Pelaksanaan Pembelajaran Seni Budaya (Tari) Daring Via Whatsapp Di SMP Negeri 11 Solok Selatan - Dita Marthisilya; Fuji Astuti (FBS Universitas Negeri Padang, 2021)
The study aims to identify and describe the implementation of learning Culture and Arts (dance) by using WhatsApp at SMP N 11 of South Solok.This is a qualitative research by using descriptive method. The research instrument was the researcher itself and was supported by additional instruments such as a laptop, a camera, and writing instruments. Types of data used in this study were primary and secondary data. The data were collected through literature study, observation, and documentation. The steps of analyzing the data were reducing the data, presenting the data, and drawing conclusions. The results show that the implementation of online Culture and Arts (dance) learning in terms of material levels and dance patterns in class VII 1 of SMP N 11 South Solok by using WhatsApp runs very well although it is not maximized. This is due to the fact that the Basic Competence 4 could not be implemented. Judging from the planning, the learning design carried out by teachers remains the same but the steps for implementation are different because the learning system uses WhatsApp application. Teachers are more flexible in using media for learning. Teachers used to only use textbook media, now the media used are more interesting with the use of power points and videos from YouTube sent to WhatsApp group. In terms of assessment, it is conducted by looking at the assignments submitted by students and quiz scores. In term of implementing learning materials of knowledge, basic competence 3 is carried out very well. It is seen from the results of the assignments submitted by the students. There are no students whose grades were below the cut score. Even though in the submission of the assignments students are often not on time because of the internet’s load problem, the results of the submitted assignments are good enough and can even be more than the materials provided by the teacher. This proves that the students can look for additional materials other than what the teachers provide.